Workplace accidents and workers' solidarity: mutual health insurance in early twentieth‐century Sweden†. (8th July 2021) - Andersson, Lars Fredrik; Eriksson, Liselotte; Nystedt, Paul
Abstract: During the industrialization period, the rate of workplace‐related accidents increased. Because of the lack of public insurance, mutual health insurance societies became the main providers of workplace accident insurance among workers. Due to large differences in accident risk, health insurance societies were potentially exposed to the risk of adverse selection, since they employed equal pricing for all members regardless of risk profile. This article investigates the impact of workplace accident risk on health insurance selection and outcomes. We employ household budget surveys encompassing urban workers in Sweden during the early twentieth century. We find evidence for a redistribution from low‐ to high‐risk‐exposed workers, as workplace accident risk had a significant and positive impact on receiving health insurance benefits, also when controlling for a variety of factors. Workers exposed to greater risks in the workplace were more likely to have health insurance but did not pay higher premiums. The redistribution from low‐ to high‐risk‐exposed workers was largely accepted and viewed as an act of solidarity between workers. Given that health insurance societies were aware of this redistribution, we argue for the presence of informed, rather than adverse, selection.